Protein Kinase D1 (PKD1) Is a New Functional Non-Genomic Target of Bisphenol A in Breast Cancer Cells - Merzoug-Larabi, Messaouda; Youssef, Ilige; Bui, Ai Thu; Legay, Christine; Loiodice, Sophia; Lognon, Sophie; Babajko, Sylvie; Ricort, Jean-Marc (Frontiers in Pharmacology, 2020)
Exposure to bisphenol A (BPA), one of the most widespread endocrine disruptors present in our environment, has been associated with the recent increased prevalence and severity of several diseases. BPA is suspected to act through genomic and non-genomic pathways. However, its precise molecular mechanisms are still largely unknown. Our goal was to identify and characterize a new molecular target of BPA in breast cancer cells in order to better understand how this compound may affect breast tumor growth and development. By using in vitro and in vivo models, we demonstrated that PKD1 is a functional non-genomic target of BPA. PKD1 specifically mediates BPA-induced cell proliferation, clonogenicity, and anchorage-independent growth of breast tumor cells. Additionally, low-doses of BPA (≤ 10-8 M) induced the phosphorylation of PKD1, a key signature of its activation state. Moreover, PKD1 overexpression increased the growth of BPA-exposed breast tumor xenografts in vivo. These findings further our understanding of the molecular mechanisms of BPA. By defining PKD1 as a functional target of BPA in breast cancer cell proliferation and tumor development, they provide new insights into the pathogenesis related to the exposure to BPA and other endocrine disruptors acting similarly.